Response surface models for the influences of product and process variables on quality deteriorations in heated orange juice - Corook, Mark Lester F. (College of Home Economics, University of the Philippines Diliman, 2014)
Finished product quality attributes are significantly influenced by intrinsic raw material characteristics and the parameters applied during processing. In this study, the individual and interactive influences of intrinsic product characteristics, such as soluble solids, total acidity and dilution; and extrinsic process parameters, including heating temperature and time on the quality attributes of heat-treated ponkan (Citrus sinensis) juice namely ascorbic acid activity and Commission Internationale I'Eclairage (CIE)-measured and derived color parameters were determined. The Central Composite Rotatable Design of Experiment was employed to determine the combinations of the experimental variables applied onto ponkan juice. Predictive models were developed and analysed through Response Surface Methodology. The models used were also subjected to mathematical and graphical validation. Results showed that residual ascorbic acid activity after heat treatment (AA) and ascorbic acid loss/degradation (ΔAA) were both significantly influenced by the individual linear effects of (n=10) heating temperature and heating time. AA and ΔAA values in all validating systems for the predictive models for AA and ΔAA were able to be adequately estimated. For the measured and derived CIE color parameters, the linear influence of dilution significantly influenced all responses; while only b*, Δb*, C* and ΔC* were significantly influenced by the quadratic effect of dilution. The linear effect of soluble solids significantly affected L* and ΔL*, while its quadratic effect influenced b*, Δb*, C* and ΔC*. No significant interactive influence of any tested variable in any measured response was observed. Furthermore, time and temperature ranges tested in this work did not have significant effects in the responses measured. Validation of the developed models showed that predictive efficiencies for L*, a*, b*, h° and C* were within acceptable limits. The results obtained from this work contribute to further understanding of quality degradation in heat-treated Citrus sinensis juice for better control of food quality.